Pseudomonas aeruginosa and lung function decline in patients with bronchiectasis. (March 2021) - Martinez-García, M.A.; Oscullo, G.; Posadas, T.; Zaldivar, E.; Villa, C.; Dobarganes, Y.; Girón, R.; Olveira, C.; Maíz, L.; García-Clemente, M.; Sibila, O.; Golpe, R.; et al.
Abstract: Objectives: The objective of this study was to analyse lung function decline over time in bronchiectasis, along with the factors associated with it. Methods: Spirometry was measured every year in this observational, prospective study in 849 patients from the Spanish Bronchiectasis Registry (RIBRON). The main outcome was the decline in the rate of forced expiratory volume during the first second (FEV1). To be included in this study, patients needed a baseline assessment and at least one subsequent assessment. FEV1 decline was analysed using a mixed-effects linear regression model adjusted for clinically significant variables. Results: We recruited 849 bronchiectasis patients with at least two annual lung function measurements (follow-up range 1–4 years). A total of 2262 lung function tests were performed (mean 2.66 per patient, range 2–5). Mean baseline FEV1 was 1.78 L (standard deviation (SD) 0.76; 71.3% predicted). Mean age was 69.1 (SD 15.4) years; 543 (64% women. The adjusted rates of FEV1 decline were –0.98% predicted/year (95% confidence interval (CI) –2.41 to –0.69) and –31.6 (95% CI –44.4 to –18.8) mL. The annual FEV1 decline was faster in those patients with chronic bronchial infection by Pseudomonas aeruginosa (–1.37% (52.1 mL) vs –0.37% (–24.6 mL); p < 0.001), greater age, increased number of severe exacerbations in the previous year and higher baseline FEV1 value. Discussion: In patients with bronchiectasis, the annual rate of FEV1 decline was –31.6 mL/year and it was faster in older patients and those with chronic bronchial infection by P. aeruginosa, increased number of previous severe exacerbations and higher baseline FEV1 value.